Nitrate-dependent Uranium mobilisation in groundwater - Bonotto, Daniel Marcos [UNESP] (2019)
Nitrate is a critical substance that determines the prevailing redox conditions in groundwater, and in turn the behaviour of Uranium (U). Therefore, the excessive use of nitrate-fertiliser in agricultural catchments could exert a significant influence on U mobilisation. This is a significant issue in catchments, where groundwater resources are increasingly being exploited for drinking water production. Past studies on U mobility in groundwater have considered individual hydro-geochemical factors influencing U concentrations, rather than as a single system with multiple factors. This research study investigated nitrate-dependent U mobility within a catchment in Brazil, where a range of intensive agricultural activities are undertaken and the giant Guarani aquifer is located. The study used direct measurements of groundwater redox conditions and other hydro-geochemical parameters. The research outcomes indicated that U could have two hydro-geochemical systems based on positive and negative redox potential of groundwater. The pH, HCO3 − and temperature pose the largest influence, respectively, on U mobilisation, and these impacts are greater in agricultural lands than urban areas. Acidic and less reducing (positive redox) groundwater across the aquifer and basic and highly reducing (negative redox) groundwater in agricultural areas make U more mobile. The alkalinity increases U mobility in less reducing groundwater across the aquifer and in highly reducing groundwater in agricultural areas. Further, U can be mobile in hot and less reducing groundwater across the aquifer, but hot and highly reducing groundwater in agricultural areas can limit U mobility. More importantly, the study revealed that U can be mobile under high NO3 − concentrations in reducing groundwater in non-agricultural areas. However, anthropogenic inputs of NO3 − are expected to be lower than natural NO3 − inputs in areas where the groundwater is highly reducing. Hence, fertiliser use in agricultural lands is less likely to increase U mobility in highly reducing groundwater.